COMPARISON OF COSTS AND INCOME OF OPEN HOUSE WITH CLOSE HOUSE IN SETUTA VILLAGE, JANAPRIA DISTRICT, LOMBOK CENTRAL DISTRICT - Yuliana Ashri (Fakultas Pertanian, Universitas Gunung Rinjani, 2022)
This study aims to 1) determine the difference in costs incurred by broiler farmers with open house and close house systems, 2) To determine the difference in income of broiler farmers with open house and close house systems. The method used in this research is descriptive method with data collection using questionnaires and interviews. This research was carried out in Setuta Village, Janapria District, Central Lombok Regency with the consideration that of the 12 villages in Janapria District that conduct broiler chicken farming, Setuta Village mostly conducts livestock business with close house and open house systems. The results showed that the average total cost incurred by farmers using the open house system was Rp. 40,574/head or Rp. 85,203,809/period with an average number of chickens of 2,100. As for the close house system breeders, the costs incurred are IDR 40,803/head or IDR 244,815,170/period with an average number of 6,000 chickens. The average income received by farmers with open house systems is Rp. 3,861/head or Rp. 8,108,646 /period with an average number of chickens of 2,100, while farmers with close house systems are Rp. 6,000/head or Rp. 41,844,051/period. with an average of 6000 chickens.